A river between us [videorecording (DVD)] - Atkinson, Jason A.; Martin, Jeff (Film director) (Green Planet Films : Virgil Films, 2015)
Documents the largest river restoration project in American history, the struggle to remove four dams on the Klamath River in California and Oregon.